2017
DOI: 10.1002/celc.201701039
|View full text |Cite
|
Sign up to set email alerts
|

An Omni‐healable and Tailorable Aqueous Lithium‐Ion Battery

Abstract: Reliability and safety are critical issues for portable power sources aiming for next-generation electronics. However, most lithium-ion batteries (LIBs) will fail to work or will cause safety problems after physical damage or violent deformation. Here, an omni-healable aqueous LIB, which can self-repair its electrodes and electrolyte simultaneously after mechanical breakage, is fabricated by integrating all of the electroactive components into polymer networks cross-linked by dynamic borate ester bonding. Once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…It was found that after being cut into two pieces, the Li‐ion battery could be recovered within a few seconds and the electrochemical performances maintained 17.2 mAh g −1 at 0.5 A g −1 after 5th cycle of cutting/healing, compared with the initial capacity of 28.2 mAh g −1 . In Figure , another example of Omni‐healable aqueous Li‐ion battery was proposed by Hao et al through the integration of both electrode and electrolyte materials into dynamic borate ester bonding crosslinked polymeric networks . The self‐healable electrode materials were fabricated through crosslinking N , N , N ‐trimethyl‐1‐(oxiran‐2‐yl) methanaminium chloride grafted PVA‐based polymeric materials (PVA‐g‐TMAC) with borax in the presence of the electrode materials.…”
Section: Hydrogel Electrolytes For Aqueous Li‐ or Na‐ion Storagesmentioning
confidence: 97%
See 3 more Smart Citations
“…It was found that after being cut into two pieces, the Li‐ion battery could be recovered within a few seconds and the electrochemical performances maintained 17.2 mAh g −1 at 0.5 A g −1 after 5th cycle of cutting/healing, compared with the initial capacity of 28.2 mAh g −1 . In Figure , another example of Omni‐healable aqueous Li‐ion battery was proposed by Hao et al through the integration of both electrode and electrolyte materials into dynamic borate ester bonding crosslinked polymeric networks . The self‐healable electrode materials were fabricated through crosslinking N , N , N ‐trimethyl‐1‐(oxiran‐2‐yl) methanaminium chloride grafted PVA‐based polymeric materials (PVA‐g‐TMAC) with borax in the presence of the electrode materials.…”
Section: Hydrogel Electrolytes For Aqueous Li‐ or Na‐ion Storagesmentioning
confidence: 97%
“…In addition, self‐healable Li‐ion batteries based on self‐healing hydrogels were also reported . For example, Zhao et al reported a self‐healing aqueous Li‐ion battery based on self‐healing polymeric substrate and aqueous lithium sulfate/sodium carboxymethylcellulose (Li 2 SO 4 /CMC) gel electrolyte, as shown in Figure .…”
Section: Hydrogel Electrolytes For Aqueous Li‐ or Na‐ion Storagesmentioning
confidence: 99%
See 2 more Smart Citations
“…After self‐healing for 20 min, a damaged LIB could still regain 98.7% of its original mechanical strength, showing its high self‐healing efficiency. Furthermore, the cell had high elastic strain and could also be tailored into arbitrary shapes while maintaining its electrochemical performance …”
Section: Smart Materials With Self‐healing Functions For Libsmentioning
confidence: 99%